Board Committes for Improving Corporate Governance: A Necessity - Pasricha, J. S.; Chauhan, Shikha (Prabandhan: Indian Journal of Management, 2009)
Modern day corporations are working on market based philosophy. Globalization and liberalization of economies has opened a number of opportunities and challenges for the corporate entities. The success of any company in the present scenario depends upon system of corporate governance prevailing in it. In fact the system of corporate governance prevailing in corporate entities shapes the growth and future of not only of a business enterprise but also of capital market and economy as such. The growing specialization and complexity of modern day business make it difficult for directors to deal with each and every matter of business. Hence the companies are realizing the need for establishing separate committees of the board to deal with specific tasks. Through this paper an attempt has been made to study the types of committees set up by Indian companies besides the ones which have been made mandatory by the clause 49 of the listing agreement and Companies Act 1956. Setting up of different sub committees of board depends upon the nature and requirements of the company. For the purpose of study, 70 companies were selected consisting of 35 companies each from Pharmaceutical and Information Technology sector. The annual reports of these sample companies for the period of six years 2001-02 to 2006-07 have been examined to study kind of committees formed by them to improve governance practices. Findings revealed that different types of committees have been constituted by sample companies depending upon their needs but number of companies constituting the board sub-committees was very small. Keeping in view the role and functions performed by these committees in sample companies, it is suggested that few committees like risk management committee, nomination committee and corporate governance committee should be made mandatory for the listed companies.